Pelatihan Pemanfaatan Software Pendukung Dalam Pembuatan Artikel Ilmiah Terpublikasi Bagi Guru-Guru SMA - Herlawati, Herlawati; Atika, Prima Dina; Hendharsetiawan, Andy Achmad; Handayanto, Rahmadya Trias; Sumadyo, Malikus; Whidhiasih, Retno Nugroho; Ekawati, Inna; Irwan, Dadan; Haryono, Haryono (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
Supportive software for scientific article creation is an application that assists in writing scientific articlesefficiently and effectively. This software features reference management, note-taking, text review, andformatting according to academic standards. The training to be provided will focus on creating scientificarticles using supportive software to enhance the competence of teachers in publishing their scientific articles.By understanding how to create scientific articles, high school teachers can improve their academic abilities,serve as positive examples for students, provide resources, and contribute to research and educationaldevelopment. This can help improve the quality of education and produce competent and skilled students. Theproposed solution is to organize training on the utilization of supportive software in scientific article creation.This training will provide understanding and skills in using software such as Mendeley and ChatGPT. Mendeleyis a reference management software that assists in collecting, managing, and storing references for scientificarticles. Additionally, Mendeley helps organize references according to various writing styles such as APA,MLA, Chicago, Vancouver, and IEEE. ChatGPT, on the other hand, is a natural language model that helpsgenerate structured and meaningful texts. In the context of scientific article creation, ChatGPT can assist informulating and organizing ideas or concepts, as well as providing suggestions or feedback for scientificwriting. Both of these software options can be chosen based on the needs and preferences of the writer. Theresults of this training, based on a survey using an online mentimeter, showed that it was very useful and theparticipants wanted to continue this training.